Rediscovered of Gnetum gnemon var. tenerum Markgr. in Kalimantan - Astuti, Inggit Puji; Witono, Joko Ridho (Perhimpunan Biologi Indonesia, 2016)
SHORT COMMUNICATIONRediscovered of Gnetum gnemon var. tenerum Markgr. in Kalimantan